Pengaruh Profitabilitas, Likuiditas, Dan Ukuran Perusahaan Terhadap Kebijakan Dividen Pada Perusahaan Food And Beverage Yang Terdaftar Di BEI Tahun 2019-2021 - Bayu Prasetyo; Sri Layla Wahyu I (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2023)
This study aims to determine whether the effect of profitability, liquidity, and company size on dividend policy in food and beverage companies listed on the IDX in 2019-2021. The research data obtained a sample of 12 companies for 3 (three) years, so the number of observations was 36. The data analysis method used was multiple linear regression analysis. The data used in this study is secondary data, namely in the form of financial reports obtained from the official IDX website: www.idx.co.id. Hypothesis testing uses a significance level. The results showed (1) profitability has a negative effect on dividend policy, (2) liquidity has a positive effect on dividend policy, (3) firm size has a negative effect on dividend policy.The estimation result of the regression test of determination show an adjusted R2 value of 0.298. This means that profitability , liquidity, and company size in this regression model are able to explain variations in debt policy of 29,8%, while 70,2% are explained by other factors not included in this research model.